2016
DOI: 10.1007/s00192-016-3175-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between age and pelvic organ prolapse bother

Abstract: Women in the 6th and 7th decades of life experience higher levels of bother from POP than older or younger women with the same stage of prolapse. This suggests that women in these decades of life might be at a higher risk for impairment of quality of life from POP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
0
19
0
2
Order By: Relevance
“…The findings of this study showed that the expression of klotho was significantly down-regulated in the pelvic tissue fibroblasts collected from patients with pelvic organ prolapse (POP), at both the mRNA and protein expression levels. There is increasing evidence for the relationship between the expression of klotho proteins and POP, as both of them are associated with the aging process [1619]. POP is more common in elderly women [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this study showed that the expression of klotho was significantly down-regulated in the pelvic tissue fibroblasts collected from patients with pelvic organ prolapse (POP), at both the mRNA and protein expression levels. There is increasing evidence for the relationship between the expression of klotho proteins and POP, as both of them are associated with the aging process [1619]. POP is more common in elderly women [16].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence for the relationship between the expression of klotho proteins and POP, as both of them are associated with the aging process [1619]. POP is more common in elderly women [16]. Klotho protein expression has been shown to have a role in the suppression of several aging phenotypes, including muscle atrophy [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is ubiquitous that the increase by weight contributes harmful influence on health of females and it also contributes to POP pathogenesis. The studies of Bradley and Kudish suggested that obesity was risky for POP and increase of BMI bring higher morbidity [36,37]. Another important risk factor is vaginal delivery.…”
Section: Plos Onementioning
confidence: 99%
“…The risk of POP increases with age, reaching a peak in individuals aged 60–69 years ( 3 ). A sample study previously revealed that women in the 60–70 years age group experience higher levels of distress from POP compared with those in younger women regardless of the stage of prolapse ( 4 ). Pelvic organs are connected and are supported by the levator ani muscle complex, cardinal and uterosacral ligament (USL), endopelvic fascia and the pelvis itself ( 3 ).…”
Section: Introductionmentioning
confidence: 99%